The Impact of China’s Digital Finance on R&D Investment and Regional Innovation Performance - Zhang, Shaohe; Nunthasen, Ke; Sinnarong, Nirote; Nunthasen, Warapon (Rajapark Journal, 2024)
We use a mediation effect model to explore the impact of digital finance on regional innovation based on the China digital finance index and interprovincial panel data from 2011 to 2021. We find that the development of digital finance in China is conducive to promoting regional innovation performance, and there is regional heterogeneity. The breadth of digital finance coverage does not significantly impact regional innovation performance. In contrast, the depth and degree of digital finance use substantially impact regional innovation performance. The impact of digital finance on regional innovation performance is not significant in the eastern region but is more important in other regions. At the same time, digital finance promotes regional innovation performance through the intermediary effect of R&D investment, and R&D investment plays a mediating role in promoting regional innovation performance through the depth of digital finance use and the degree of digital support services. The Chinese government should fully understand the role and mechanism of digital finance in promoting regional innovation performance, formulate targeted and differentiated regional development policies, and help digital finance achieve regional innovation performance while developing digital finance.